2006
DOI: 10.1007/s00011-006-6074-2
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive low-dose doxycycline therapy effect on clinical parameters and gingival crevicular fluid tissue plasminogen activator levels in chronic periodontitis

Abstract: These results provide additional information about usefulness of LDD therapy as an adjunct to nonsurgical therapy in long-term management of periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 52 publications
(111 reference statements)
1
29
0
1
Order By: Relevance
“…However, it is not clear how this modulation takes place or what role cytokines and chemokines play during this process. Based on these reports and results of our previous studies, 6,14‐17 we have therefore hypothesized that the cytokine‐chemokine network responds to SDD and changes can be detected in GCF. The aims of the present study are to investigate the effect of non‐surgical periodontal therapy with or without adjunctive SDD on the clinical parameters and GCF cytokine‐chemokine levels in subjects with chronic periodontitis and to monitor the long‐term study results for 12 months.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…However, it is not clear how this modulation takes place or what role cytokines and chemokines play during this process. Based on these reports and results of our previous studies, 6,14‐17 we have therefore hypothesized that the cytokine‐chemokine network responds to SDD and changes can be detected in GCF. The aims of the present study are to investigate the effect of non‐surgical periodontal therapy with or without adjunctive SDD on the clinical parameters and GCF cytokine‐chemokine levels in subjects with chronic periodontitis and to monitor the long‐term study results for 12 months.…”
mentioning
confidence: 76%
“…Subantimicrobial‐dose doxycycline (SDD) therapy is an effective means in the management of periodontitis by modulating the host response when used as an adjunct to non‐surgical periodontal therapy. Many studies have demonstrated the efficacy of SDD on matrix metalloproteinase (MMP) production and collagen metabolism, arresting the progression of periodontitis and preventing bone loss 13‐20 . MMPs most likely mediate the destruction of periodontal tissues through the inflammatory response where cytokine and chemokine networks play major roles, and coordination of the immune response is critical 21 .…”
mentioning
confidence: 99%
“…A decrease in clinical inflammation is observed in patients consuming Periostat, a capsule containing 20 mg doxycycline. Periostat should be used along with other bacterial removal therapies (Emingil et al, 2006). Various marketed periodontal products are shown in Table 9.…”
Section: Low-dose Antibioticsmentioning
confidence: 99%
“…Mais, les résultats à long terme avec cette forme d'administration locale de tétracyclines restent inconnus. Une autre formule thérapeutique a été testée ces dernières années ; il s'agit de l'administration de dose sous-antimicrobienne de doxycycline [64,65]. Une méta-analyse récente [66] évaluant l'efficacité de cette thérapeutique à court terme (3 mois d'administration journalière et 9 mois de suivi post-thérapeutique, a montré son efficacité sur la réduction de la profondeur de poche et un gain d'attache significatif à court terme (1 année).…”
Section: Antibiotiques En Maintenanceunclassified